Disease in Babylonia - Finkel, Irving L.; Geller, Markham J. (Cuneiform Monographs, 2007)
This collection of articles is the first collection of studies on the specific subject of disease in Babylonia, based upon actual medical texts, with contributions by senior scholars who have spent years working on published and unpublished cuneiform medical texts. The volume contains editions of unpublished materials as well as syntheses of information about specific diseases in Babylonia, such as fever, published here for the first time. The volume will be important for anyone interested in the history of ancient medicine as well as being an important contribution to Assyriology.